Multi-Level Comparative Framework Based on Gene Pair-Wise Expression Across Three Insulin Target Tissues for Type 2 Diabetes - Sun, Shaoyan; Sun, Fengnan; Wang, Yong (Frontiers in Genetics, 2019)
Type 2 diabetes (T2D) is known as a disease mainly caused by gene alterations characterized by insulin resistance, thus the insulin-responsive tissues are of great interests for T2D study. It’s in pressing need to systematically investigate commonalities and specificities of T2D among multiple tissues. Here we establish a multi-level comparative framework across three insulin target tissues (white adipose, skeletal muscle, and liver) to provide a better understanding of T2D. Starting from the ranks of gene expression, we construct the ‘disease network’ through detecting diverse interactions to provide a well-characterization for disease affected tissues. Then, we apply random walk with restarts algorithm to the disease network to prioritize its nodes and edges according to their association with T2D. Finally, we identified a merged core module by combining the clustering coefficient and Jaccard index, which can provide elaborate and visible illumination about the common and specific features for different tissues at network level. Taken together, our network-, gene-, and module-level characterization across different tissues of T2D hold the promise to provide a broader and deeper understanding for T2D mechanism.